Visual mismatch negativity in the dorsal stream is independent of concurrent visual task difficulty - Kremlacek, Jan; Kuba, Miroslav; Kubová, Zuzana; Langrová, Jana; Szanyi, Jana; Vít, František; Bednar, Michal (Frontiers in Human Neuroscience, 2013)
The manipulation of attention can produce mismatch negativity-like components that are not necessarily connected to the unintentional sensory registration of the violation of probability-based regularity. For clinical purposes, attentional bias should be quantified because it can vary substantially among subjects and can decrease the specificity of the examination. This experiment targets the role of attention in the generation of visual mismatch negativity (vMMN). The visual regularity was generated by a sequence of two radial motions while subjects focused on visual tasks in the central part of the display. Attentional load was systematically varied and had three levels, no-load, easy, and difficult. Rare, deviant, and frequent standard motions were presented with a 10/60 ratio in oddball sequences. Data from 12 subjects was recorded from 64 channels and processed. vMMN was identified within the interval of 142–198 ms. The mean amplitude was evaluated during the aforementioned interval in the parietal and fronto-central regions. A general linear model for repeated measures was applied to the mean amplitude with a three-factor design and showed a significant difference [F(1, 11) = 17.40, p = 0.002] between standard and deviant stimuli and between regions [F(1, 11) = 8.40, p = 0.01]; however, no significant effect of the task [F(2, 22) = 1.26, p = 0.30] was observed. The unintentional detection of irregularity during the processing of the visual motion was independent of the attentional load associated with handling the central visual task. The experiment did not demonstrate an effect of attentional load manipulation on mismatch negativity (MMN) induced by the motion-sequence, which supports the clinical utility of this examination. However, used stimulation paradigm should be further optimized to generate mismatch negativity that is stable enough to be usable not only for group comparisons but also for a single subject assessment.